PROBLEMATIC ASPECTS OF THE DECLARATION OF THE DEFENDANT DURING THE CRIMINAL PROCEDURE - Espinoza Bonifaz, Renzo (2019)
The research article describes and specifies the guarantees that must be observed in an unrestricted manner during the declaration of the accused during the preparatory investigation stage, and the trial. It also seeks to establish whether the reading of the previous statements of the accused during the trial affects their right to remain silent. In the same way, it tries to specify how the contradictory statements of the accused should be evaluated during the criminal process. Finally, it seeks to determine whether the statement provided by the accused during the criminal process has evidentiary aptitude to be assessed by the jurisdictional body.